PERBANDINGAN VARIASI MEDIA FILTER NON ALAMI PADA PENJERNIH AIR SARANG TAWON TERHADAP pH DAN TDS - Anggraeni, Devi; Jaya, Allan Restu; Nindito, Dwi Anung (Fakultas Teknik Universitas Palangka Raya, 2024)
Water is a variety of needs in everyday life. Raw water in Palangka Raya City is still influenced by peat water which has a low pH, while river water has quite high turbidity due to sedimentation. For residential areas that are far from the reach of PDAM, it will be difficult to get clean water and there is no fast technology to handle the decrease in acidity. An alternative innovation that can be used by people who are far from the reach of PDAM is to use appropriate technology tools for wasp nest water purifiers. The purpose of the study was to obtain a comparison of water treatment results from several variations of non-natural filter media in wasp nest water purifiers against pH and TDS. The method used in this experimental test was to test short, medium, and high wasp nest water purifiers with a filtration hole size of 0.25 cm and a distance between holes of 0.5 cm. The volume of non-natural filter media in various sizes of wasp nest water purifiers was conditioned the same in each experiment. The filtration process uses 4 pumps with a pump discharge of 45 l/minute each. The results obtained indicate that the filtration type water purifier functions well and is able to increase pH. There is an increase in the TDS parameter because during the water circulation process there is uncontrolled mixing of the filter media.